The failing kidney allograft: A review and recommendations for the care and management of a complex group of patients. Issue 9 (19th July 2021) - Lubetzky, Michelle; Tantisattamo, Ekamol; Molnar, Miklos Z.; Lentine, Krista L.; Basu, Arpita; Parsons, Ronald F.; Woodside, Kenneth J.; Pavlakis, Martha; Blosser, Christopher D.; Singh, Neeraj; Concepcion, Beatrice P.; Adey, Deborah; et al.
Abstract : The return to dialysis after allograft failure is associated with increased morbidity and mortality. This transition is made more complex by the rising numbers of patients who seek repeat transplantation and therefore may have indications for remaining on low levels of immunosuppression, despite the potential increased morbidity. Management strategies vary across providers, driven by limited data on how to transition off immunosuppression as the allograft fails and a paucity of randomized controlled trials to support one approach over another. In this review, we summarize the current data available for management and care of the failing allograft. Additionally, we discuss a suggested plan for immunosuppression weaning based upon the availability of re‐transplantation and residual allograft function. We propose a shared‐care model in which there is improved coordination between transplant providers and general nephrologists so that immunosuppression management and preparation for renal replacement therapy and/or repeat transplantation can be conducted with the goal of improved outcomes and decreased morbidity in this vulnerable patient group. Abstract : In the context of the failing allograft, the authors focus on preparation for return to dialysis and/or retransplantation, personalization of immunosuppression weaning, reduction of sensitization risk in anticipation of repeat transplantation, and optimization of shared care between transplant providers and general nephrologists.